KEPEMILIKAN DAN PENGUASAAN MANFAAT DALAM PERSPEKTIF FUQAHA - Armiadi Musa (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
There are various understandings of the meaning of benefits, whether it can be categorized as property or not. The musalabi and Wahbah al-Zuhayli mushafa are of the same opinion about the benefits despite the different editorials, namely the usefulness or usefulness produced from a particular object, such as inhabiting a house, driving a car, wearing clothes, etc., while the Prophet Ahmad Al-Zarqa states that the benefits is the essence of ownership of property and objects with 'haq al-intifa', which is more common because the more includes the beneficial properties also includes 'haq al-intifa' which is something that benefits obtained from the permission of the owner, without ownership of the object. According to Hanafiyah, benefits other than the aqad ijarah are considered not valuable, in contrast to Syafi'iyah and Hanabilah who argue that the benefits of an object lie in the object itself, because that is the purpose of using the object. And mastery of the benefits of al-ijarah, al-'ariah, al-waqaf, al-washiyah bi al-manfaah and al-ibahah can switch after the benefits are exchanged for rewards and benefits of an object must be handed over.